Using Bibliocounseling to Improve High-School Student’s Social Intelligence - Laily Tiarani Soejanto; Eva Kartika Wulan Sari; Silvianingsih Silvianingsih (Universitas PGRI Semarang, 2020)
ABSTRACTThis study aims to: 1) determine the level of student’s social intelligence before the application of bibliocounseling technique, 2) determine the level of student’s social intelligence after the application of bibliocounseling technique, and 3) determine the effectiveness of bibliocounseling technique in improving student’s social intelligence. This research used quantitative approach with pretest and posttest quasi-experimental design withs samples of 12 students who were netted using purposive sampling techniques. The research instrument used is the scale of social intelligence. The data were analyzed using Wilcoxon non parametric test statistics. The results show that 1) the level of student’s social intelligence before receiving bibliocounseling technique were in the low category, 2) after using the bibliocounseling technique, the level of student’s empathy had shifted to the high category, 3) bibliocounseling technique were proven to be effective in improving students' social intelligence. Suggestions submitted in this study are: 1) for counselors to use bibliocounseling technique as one of alternative strategy to help high-school students to have a qualified social intelligence, 2) high-school counselors can implement bibliocounseling materials that are conform with students' social intelligence problems, 3) other researchers could develops bibliocounseling guidebook that based on the technique implemented in this research.